Effect of shear-thinning behavior on flow regimes in Taylor-Couette flows - Elcicek, Huseyin; Guzel, Bulent (ELSEVIER, 2020)
Taylor-Couette reactors may offer an alternative treatment method for ballast water treatment or for flocculation of small size particles to be removed in water treatment processes due to created high energy dissipation and momentum transfer by Taylor vortices occurred during transitional flow regimes. In this study, the effect of shear-thinning behavior on flow structures and transition thresholds in Taylor-Couette flows for narrow and wide gaps is experimentally investigated using xanthan solutions. The experiments presented in this paper establish the existence of non-axisymmetric flow structures before the Taylor vortex flow regime and an instability threshold to the modified wavy vortex flow from Taylor vortex flow in shear-thinning fluids i.e. altering the instability mechanisms. The critical Reynolds numbers for the first and second instabilities and the structural characteristics of the flow states were identified for Newtonian and shear thinning fluids in comparison. The vortices have varying axial wavelength and also drift along the axis in shear-thinning fluids. The variation of the critical Reynolds number with the shear-thinning index has been shown through three different Reynolds number definitions. It is shown that when the Reynolds number is defined using single preferred value of radially varying viscosity, decreasing shear-thinning index may delay the appearance of Taylor vortices depending on the gap ratio. When the local Reynolds numbers defined based on the local viscosity have been taken into account, shear thinning effect has a monotonic effect on the critical Reynolds number which decreases with decreasing shear-thinning index for both narrow and wide gaps in transition to Taylor vortex flow regime.
Keywords: Taylor-Couette; Non-Newtonian fluids; Transition; Shear-thinning; Flow regimes; LAMINAR-TURBULENT TRANSITION; STABILITY; INSTABILITY; VORTICES; DYNAMICS; FLUID; WAVY; Mechanics